P-Nitro-tetradecyloxy-calix[4]arene as a highly selective stationary phase for gas chromatographic separations. (21st October 2019) - Sun, Tao; Shuai, Xiaomin; Bin, Li; Ren, Kaixin; Jiang, Xingxing; Chen, Haipeng; Hu, Shaoqiang; Cai, Zhiqiang
Abstract : Here, we report the first example of the utilization of p -nitro-tetradecyloxy-calix[4]arene (C4A-NO2 ) as a stationary phase for capillary gas chromatographic (GC) separations. Abstract : Here, we report the first example of the utilization of p -nitro-tetradecyloxy-calix[4]arene (C4A-NO2 ) as a stationary phase for capillary gas chromatographic (GC) separations. The statically coated C4A-NO2 column exhibited a high column efficiency of 3815 plates per m and moderate polarity. The C4A-NO2 column was investigated for its separation performance and retention behaviours by utilizing a wide variety of isomer mixtures, covering alkylated benzenes and naphthalenes, alkenes, furans, alcohols, benzaldehydes, phenols and halogenated anilines. Importantly, the C4A-NO2 column exhibited high resolving capability for both aliphatic and aromatic isomers. Particularly, it displayed advantageous resolving capability over the commercial DB-17 column for halogenated aniline isomers. This work provides a good reference for designing calixarene derivatives as GC stationary phases, which is important for developing a family of stationary phases with specific selectivity.